Menggali Makna Kalyanamitta Peran dan Konteks dalam Sigalovada Sutta dan Visuddhimagga - ratna sari, dwi; Setiawan, Ari; Astika, Ria; Susanto, Susanto; Sumarwan, Edi (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
The concept of kaly namitta, or good friend, is a very important part of Buddhist teachings. Two classic texts in the Buddhist canon, Sigalovada Sutta and Visuddhimagga, highlight the different but no less important role of kaly namitta in the spiritual development of a person. In Sigalovada Sutta, kaly namitta is described as a true friend who influences individual moral progress in everyday life. Sigalovada, the main character in the sutta, was instructed by the Buddha about the importance of choosing friends wisely, who would support the individual in developing good behavior and morality. Visuddhimagga emphasizes Kalyanamitta's role as a meditation teacher. In this context, Kalyanamitta acts as a spiritual guide who guides a person's meditation practice to inner peace and a deeper understanding of true reality. The meditation teacher in the Visuddhimagga is seen as a figure who holds a crucial role in the spiritual journey of a practitioner, guiding them through the various stages of meditation towards enlightenment. The differences in the emphasis on the role of Kalyanamitta in both texts describe different contexts and purposes in the teachings of Buddhism. Sigalovada Sutta emphasizes the importance of true friends in everyday life and their relationship with moral progress, while Visuddhimagga highlights the role of a meditation teacher in a person's spiritual development. However, these two concepts complement each other in one's attempt to a deeper enlightenment and understanding of Dhamma.This study uses a library study method with a Buddhist approach to analyze the differences between the concepts of kaly namitta in the two texts. The results confirm the importance of a proper understanding of these differences to avoid misunderstandings and deepen the depths of Buddhism.